2005
DOI: 10.1016/j.jvs.2005.05.003
|View full text |Cite
|
Sign up to set email alerts
|

Lower extremity minor amputations: The roles of diabetes mellitus and timing of revascularization

Abstract: Although minor amputations can lead to limb preservation in most patients, the performance of a revascularization subsequent to amputation, transmetatarsal as the initial amputation, and end-stage renal disease are poor prognostic indicators. Inferior long-term patient survival is most closely associated with renal insufficiency and conversion to major amputation early after the initial procedure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
58
1
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(64 citation statements)
references
References 30 publications
4
58
1
1
Order By: Relevance
“…Campbell and colleagues 20 In-hospital or 30-day mortality figures after minor amputation are less readily available, but a rate of 0·7 per cent has been published 22 , comparable with the adjusted mortality rate for minor amputation of 3·6 per cent reported here. The significant variation in adjusted in-hospital mortality rate seen across SHAs for both major and minor amputations is likely to have a multifactorial basis.…”
Section: Discussionsupporting
confidence: 70%
“…Campbell and colleagues 20 In-hospital or 30-day mortality figures after minor amputation are less readily available, but a rate of 0·7 per cent has been published 22 , comparable with the adjusted mortality rate for minor amputation of 3·6 per cent reported here. The significant variation in adjusted in-hospital mortality rate seen across SHAs for both major and minor amputations is likely to have a multifactorial basis.…”
Section: Discussionsupporting
confidence: 70%
“…14 End-stage renal disease is one of the recognized risk factors that worsen the prosthesis-wearing rate. 9,13 In this series, the renal function factor affected the preprosthetic training waiting time (P ϭ 0.001) and also influenced the daily prosthesis usage time (P ϭ 0.01). For patients with abnormal renal function (creatinine Ͼ1.4 mg/dl) that require amputation or revascularization surgery, surgeons should carefully explain the additional risks associated with abnormal renal function to the patient and families.…”
Section: Discussionmentioning
confidence: 77%
“…In patients with forefoot gangrene, attempts were made to optimize arterial perfusion to the affected extremity with revascularization, either open or endovascular, when possible. Sheahan et al 4 found that a revascularization procedure performed subsequent to partial foot amputation was a predictor of subsequent limb loss and advocated early revascularization to optimize amputation healing. In the current series, patients undergoing TMA following revascularization had healing rates no different from those of patients who underwent amputation without revascularization.…”
Section: Commentmentioning
confidence: 99%